Tone Sandhi : patterns across Chinese dialects - Chen, Matthew Y. (Cambridge University Press, 2000)
Matthew Chen's landmark study offers the most comprehensive analysis to date of the rich and complex patterns of tone used in Chinese languages. His book, the culmination of a ten-year research project, explores a range of important theoretical issues against a wealth of empirical data not previously accessible to linguists.
Keywords: Chinese language -- Tone.; Chinois (Langue) -- Ton.; FOREIGN LANGUAGE STUDY -- Chinese.; Chinese language -- Tone; Mundart; Sandhi; Chinees.; Toon (taalkunde); Dialecten.; Sandhi.; Chinois (langue) -- Ton.; Langues chinoises.; Chinois (langue) -- Intonation.; Chinois (langue) -- Phonétique.; Chinesisch.; Electronic books.